BS ISO 11119-9. Gas cylinders. Refillable composite gas cylinders and tubes. Design, construction and testing. Part 3. Fully wrapped fibre reinforced composite gas cylinders and tubes up to 450 l with non-load-sharing metallic or non-metallic liners or without liners (21st August 2019) - British Standards Institution,
No abstract available